Neurodiversity is Human Diversity, an Equity Imperative for Education - Dawson, Colleen (International Journal for Talent Development and Creativity, 2022)
This article discusses historical system structures in education that have impeded on inclusion and present pertinent historical challenges, pedagogy and beliefs that are foundational in cultivating inclusive environments today. It explores Neurodiversity, an equity imperative, as critical to shifting the culture of teaching and learning by offering a potential framework for overcoming historical systemic barriers to inclusion. Next, it discusses shared attributes of epidemiology of teacher beliefs, neuroscience and Teacher self-study as potential foundational components, complimenting Neurodiversity paradigms. Lastly, a proposed theoretical framework and suggested future research which could lead to the development of an inclusive pedagogy. Education is the cornerstone to fostering talent and creativity of each individual and it is only when the system is truly inclusive of all human diversity, can individuals flourish developing their talents.